2000
DOI: 10.1210/endo.141.6.7483
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glutamine:Fructose-6-Phosphate Amidotransferase in Rat-1 Fibroblasts Enhances Glucose-Mediated Glycogen Accumulation via Suppression of Glycogen Phosphorylase Activity*

Abstract: The hexosamine biosynthesis pathway (HBP) mediates many of the adverse effects of excess glucose. We have shown previously that glucose down-regulates basal and insulin-stimulated glycogen synthase (GS) activity. Overexpression of the rate-limiting enzyme in the HBP, glutamine:fructose-6-phosphate amidotransferase (GFA), mimics these effects of high glucose and renders the cells more sensitive to glucose. Here we examine the role of the HBP in regulating cellular glycogen content. Glycogen content and glycogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The amount of UDP-glucose in 3T3-L1 adipocytes decreased in a dose-dependent manner when the cells were treated with glucosamine. This might indicate that activation of the hexosamine biosynthesis pathway by incubation of the cells with glucosamine either stimulates processing of UDP-glucose to generate glycogen (20) or that the UDP from UDP-glucose is released for the synthesis of UDPhexosamines (21).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of UDP-glucose in 3T3-L1 adipocytes decreased in a dose-dependent manner when the cells were treated with glucosamine. This might indicate that activation of the hexosamine biosynthesis pathway by incubation of the cells with glucosamine either stimulates processing of UDP-glucose to generate glycogen (20) or that the UDP from UDP-glucose is released for the synthesis of UDPhexosamines (21).…”
Section: Discussionmentioning
confidence: 99%
“…25,54 In addition, we have shown that stable GFA overexpression is a unique model even when compared with culturing in low-dose glucosamine. 11…”
Section: Discussionmentioning
confidence: 99%
“…9 The HBP pathway and tissue concentrations of UDP-GlcNAc can be increased by various methods such as exposure to prolonged hyperglycemia, glucosamine or uridine infusion, hyperlipidemia, and GFA overexpression. [10][11][12][13] The HBP has been shown to have protean effects on glucose metabolism, insulin action, and other glucose-mediated cellular events. For example, chronic exposure of rat-1 fibroblasts to high glucose decreases both basal and insulin-stimulated glycogen synthase activity, and glucosamine or overexpression of GFA mimics the effects of high glucose.…”
mentioning
confidence: 99%
See 2 more Smart Citations